Antecedents of system purchasing in B2B services. Issue 3 (September 2016) - Immonen, Mika; Hallikas, Jukka; Pynnönen, Mikko
Abstract: This article aims to analyze the relation between business-to-business (B2B) service integration and purchasing strategies and to provide new knowledge on the antecedents of complex purchasing systems. We present the results of an empirical study in the infrastructure management sector (i.e., electricity and telecom networks), in which integrating B2B services is a current concern among network operators. In this article, we compare the influence of operational services and strategic services on the B2B relationships between service providers and customers. Highlights: Integration of strategic services influences to create a collaborative relationship. Cooperation in business development influences orientation toward system purchasing. System purchasing is related to long-term development and co-learning. A system purchasing increases the expected reliability of the service. System purchasing tends to increase the quality of the complex service systems.